GOAL SETTING THEORY: THE EFFECT OF INCENTIVE MODERATION ON INDIVIDUAL PERFORMANCE - Hartono, Yudi; Murniati, Monika Palupi (Faculty of Business, Widya Mandala Surabaya Catholic University, Indonesia, 2020)
This study uses goal-setting theory and reinforcement theory to explain the formation of individual motivation in achieving goals. Testing the effect of goal specificity used the experimental method to test the impact of goal specificity, different goal difficulty on the same quota incentive system as the 2x2x1 experimental design. This study's findings confirm the goal-setting theory shown from the higher achievement of participants' goals when participants are given specific and challenging goals than participant goals in different variations of goal specificity and goal difficulty. This study found that participants have a greater focus on goal specificity in driving goal attainment behavior. The findings of this study confirm the reinforcement theory shown from achieving goals that exceed targets. Positive consequences become arguments for individuals to do the same action